MODEL DC MOTOR FOR ELECTRIC DRIVE AUTOMATED PAYMENT MODES - and (Municipal economy of cities (Technical science), 2013)
The problems of modeling DC motor with independent excitation by applying an equivalent circuit that simplifies the process of automatic creation of the differential equations of the mathematical model of "motor - converter". The formula for calculating the equivalent circuit elements based on the parameters of the motor.